Factor Analysis of Nurses' Performance During the Covid-19 Pandemic in the Isolation Room of Sidrap - Dunggio, Abdul Rivai Saleh; Djunaedi, Djunaedi; Harfika, Meiana; Afritayeni, Afritayeni; Nurhaedah, Nurhaedah; Rahmat, Rezqiqah Aulia (International Journal of Health Sciences, 2023)
In health services, especially in the current conditions of the Covid-19 outbreak, nurses have several roles, namely as caregivers which is the main role where nurses will be actively involved 24 hours a day in providing nursing care in clinical service settings such as in hospitals. Apart from that, nurses also have a role as educators, where they act as a team of educators who provide education to patients, families and the community. The aim of this research is to analyze the influence of workload, anxiety level, and work environment on nurses' performance during the Covid-19 pandemic in the Isolation Room at Sidrap District Hospital. This research is quantitative research using a survey assessment approach with a cross-sectional design, namely research by studying the correlation between risk factors and the effects they cause by conducting an approach, survey or collecting data at one time. Based on the results of the research and data processing that has been carried out, it is concluded that there is an influence of workload, compensation, leadership on the performance of nurses during the Covid-19 pandemic in the Isolation Room at Sidrap District Hospital.